Adverse Events Associated with Risperidone Use in Pediatric Patients: A Retrospective Biobank Study - Kazeem A. Oshikoya; Robert Carroll; Ida Aka; Dan M. Roden; Sara L. Van Driest (Adis, Springer Healthcare, 2019)
Abstract Background Although risperidone is increasingly used for behavioral indications in children, the associated adverse events (AEs) are not well defined in this population. Objective We determined the incidence of and risk factors for AEs among children treated with risperidone at our institution, an academic medical center with inpatient, outpatient, generalist, and specialist pediatric care. Methods The study included children aged ≤ 18 years with ≥ 4 weeks of risperidone exposure. Data were obtained using de-identified electronic health records. AEs were defined as any untoward event attributed to risperidone reported by the patient, parent/guardian, or physician or detected following a laboratory investigation. Associations between AEs and clinical variables were determined using univariate and multivariate analyses. Results The study cohort included 371 individuals (median age 7.8 years [interquartile range 5.9-10.2]; 271 [73.0%] male). The two most common primary diagnoses were attention-deficit/hyperactivity disorder (160 [43.1%]) and autism (102 [27.5%]). The most frequent indications for risperidone were aggression (166 [44.7%]) and behavioral problems (114 [30.7%]). Altogether, 110 (29.6%) individuals had 156 AEs. Weight gain (32 [20.5%]) and extrapyramidal symptoms (23 [14.7%]) were the most common AEs. Aggression, irritability, and self-injurious behavior were positively associated with AEs, and concomitant analgesics and antibiotics were negatively associated. In multivariate analysis, associations remained significant for self-injurious behavior (adjusted odds ratio [aOR] 3.1; 95% confidence interval [CI] 1.7-5.4) and concomitant antibiotics (aOR 0.2; 95% CI 0.1-0.9). Conclusions Nearly one in three children treated with risperidone for ≥ 1 month experienced one or more AEs. Particular vigilance is warranted for children with self-injurious behavior.